(3GdLhO HGdehLhO aj TQM JMaI GdehQhO aj GdebUhQ hGdeeOhOs - (3eMeO Hf YHO Gddg, GHf eGdc GdWGFj GdLqjGfj, CHh YHO Gddg, LeGd GdOjf,J (B672 (3g` s
(3ChdgG (B:s
(3bGd GdabjQ Edi QMeI QHg eMeO Hf YHO Gddg Hf eGdc GdLjGfi HGH eG jaJM Chdg ajbUQ hjeO HGNJdGa GdeYfi s
(3BNQgG (B:s
(3hEf jbGd ajg GddhjJGL HGdLje hGdHcG eYdhe hGdUdGI GdJGeI GdOGFeI Ydi SjOfG hMHjHfG hTajYfG eMeO NGJe GdfHjjf hEeGe GdeQSdjf hGdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B4s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3GdCOHs